Platonici minores 1. Jh. volume Chr. - 2. Jh. n. Chr. : Prosopographie, Fragmente und Testimonien mit deutscher Übersetzung - Lakmann, Marie-Luise.; O'Meara, Dominic J.; Baltes, Matthias. (Philosophia Antiqua, 2017)
In Platonici minores Marie-Luise Lakmann offers a collection of all philosophers considered to be "Middle Platonists" (1st century BC to AD 2nd century). The collection includes 85 "minor" Platonists, arranged in alphabetical order, little known figures seldom discussed in modern research. For each philosopher all known facts about life and teaching are presented with a bibliography. This is followed by a collection of fragments and testimonia relating to the Platonist. Each original text is accompanied by a German translation. An appendix includes a brief presentation of all "major" Platonists of this period. The volume provides a complete conspectus of an important period in the history of philosophy, bringing together many scattered materials and throwing new light on what is already known of the Middle Platonism.